Data-Driven Approaches to Optimize Learning Experiences in Learning Factories - Christian Haposan Pangaribuan; Adele Valerry; Stephanie (International Transactions on Education Technology (ITEE), 2025)
This research investigates the application of data-driven approaches to optimize learning experiences in learning factories, a key area for advancing industrial and educational integration. The background of the study highlights the increasing relevance of data science in educational settings, particularly in learning factories, which combine practical learning environments with industrial technologies. The objective of this research is to explore how data science techniques, such as machine learning and predictive analytics, can be utilized to improve learning outcomes, efficiency, and engagement within these settings. The method involves a comprehensive analysis of student performance data collected from learning factory environments, employing statistical tools and data visualization techniques to identify patterns, trends, and areas for improvement. The results reveal that the integration of data-driven methodologies leads to enhanced learning experiences by tailoring content delivery, improving resource allocation, and providing real-time feedback to learners. The study concludes that data science can significantly optimize learning processes in learning factories by providing actionable insights that support both instructors and students in achieving better educational outcomes. These findings underscore the practical applicability of data science in real-world educational scenarios, suggesting that the use of data analytics in learning factories can bridge the gap between theory and practice, fostering a more effective and personalized learning experience.